Analisis Pengetahuan Pendamping Lansia tentang Palliative Care dengan Terapi Komplementer di PSTW Jember - Dian Ratna Elmaghfuroh; M. Arif Sholehudin; M. Farhan Setya Budi (Universitas Muhammadiyah Jember, 2022)
Background and Aim: Palliative care is one of the important public health problems, due to the increasing number of parents and is accompanied by insufficient attention to the very complex needs of the elderly, especially for the elderly who live in a nursing home without any accompanying family. So that the only hope that the elderly have is a companion for the elderly in the orphanage. This study aims to analyze the knowledge possessed by elderly companions about palliative care.Methods: This study uses a correlation design with a cross-sectional approach with a sample of 30 who are elderly companions. The instrument used is a modification of the PCQN (Palliative Care Quiz for Nursing) which has been tested for validity and reliability. Analysis of the data used in this research is spearman rho.Results: The results showed that the length of work of elderly assistants was 30% 10 years; 46.67% 11-20 years old; and 23.33% 21 years. The level of knowledge of elderly companions is good (73.3%), sufficient (10%), and less (16.7%). The correlation between the length of work and the knowledge of the elderly companion about palliative care obtained a significance value of 0.018 with a correlation coefficient of 0.428.Conclusion: There is a correlation between the length of work of elderly companions with knowledge about palliative care at PSTW Jember.